For this case we have that by definition, the equation of the line of the point-slope form is given by:
![y-y_ {0} = m (x-x_ {0})](https://img.qammunity.org/2020/formulas/mathematics/middle-school/341t0mqsoqe2qw4gy9ujekvq440bcbjm7u.png)
Where:
m: Is the slope
It is a point through which the line passes
According to the data of the statement we have two points through which the line passes:
![(x_ {1}, y_ {1}): (-4,3)\\(x_ {2}, y_ {2}): (-3, -1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/933djjfqpssb2ge902zc0ddixdtsn5w93y.png)
We found the slope:
![m = \frac {y_ {2} -y_ {1}} {x_ {2} -x_ {1}} = \frac {-1-3} {- 3 - (- 4)} = \frac {-4 } {- 3 4} = \frac {-4} {1} = - 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fpwzixzrvrusc3joc5esl2y83ygjiue8xy.png)
Thus, the equation is of the form:
![y-y_ {0} = - 4 (x-x_ {0})](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3bwq5aefmj4k498gqwrz4shntgyfrxhwac.png)
We substitute one of the points:
![y-3 = -4 (x - (- 4))\\y-3 = -4 (x + 4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yzk8usvflx5lku3n5abjbsphn1jch0go95.png)
Finally, the equation is:
![y-3 = -4 (x + 4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6xmpggbgusor1vzizdnqbjotaqopbtceef.png)
Answer:
![y-3 = -4 (x + 4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6xmpggbgusor1vzizdnqbjotaqopbtceef.png)